Temperamental corelates of depression symptoms among women group - Tylka, Jan; Szyntar, Kamila (Studia Psychologica: Theoria et praxis, 2009)
The aim of the study was to assess relationship between temperament and intensity of depression in women. Sixty women with diagnosis of depression participated in the study. All were between 22 and 57 years old. The intensity of depressive symptoms was evaluated by the Beck Depression Inventory (BDI). Temperament was assessed using the Formal Characteristic of Behaviour - Temperament Questionnaire (Zawadzki and Strelau). The following results were obtained: women with depression had higher level of perseveration and reactivity and lower activity, alertness and endurance.